Microstructural evolution of Ni–Co-xAl(-Cr) alloys fabricated by laser directed energy deposition - Haozhi Chai; Lilin Wang; Xin Lin; Weiming Huang; Chao Wang; Qiaodan Yan; Weidong Huang (Journal of Materials Research and Technology)
Understanding the microstructural evolution of Ni3Al-based alloy fabricated via laser directed energy deposition (L-DED) with varying Al content is of great significance for advancing the development and application of Ni3Al-based alloys in the field of high-temperature structural materials. In this study, Ni–Co–Al ternary and Ni–Co–Al–Cr quaternary Ni3Al-based alloy samples with different Al contents were prepared. The microstructure was observed by SEM, EDS and TEM, and the effects of Al element on microstructure, solidification behavior and precipitated phase were investigated. The results show that the variety of primary phase and the volume fraction of eutectic phase can be significantly affected by the change of Al content. Comparing Ni–Co–Al ternary and Ni–Co–Al–Cr quaternary Ni3Al-based alloys, Cr element also has obvious influence on the microstructure. The addition of Cr element can change the content of Al at eutectic point, inhibit the peritectoid reaction between β phase and γ phase and suppress the formation of γ 'phase at the phase interface.